2012
DOI: 10.1186/1755-8794-5-57
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Fetal Trisomy (NIFTY) test: an advanced noninvasive prenatal diagnosis methodology for fetal autosomal and sex chromosomal aneuploidies

Abstract: BackgroundConventional prenatal screening tests, such as maternal serum tests and ultrasound scan, have limited resolution and accuracy.MethodsWe developed an advanced noninvasive prenatal diagnosis method based on massively parallel sequencing. The Noninvasive Fetal Trisomy (NIFTY) test, combines an optimized Student’s t-test with a locally weighted polynomial regression and binary hypotheses. We applied the NIFTY test to 903 pregnancies and compared the diagnostic results with those of full karyotyping.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
196
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(207 citation statements)
references
References 35 publications
6
196
0
3
Order By: Relevance
“…The first group of studies was used for the meta-analysis on the performance of screening by cfDNA testing in screening for aneuploidies [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40]. These studies reported cfDNA results in relation to fetal karyotype from invasive testing or clinical outcome; 26 studies examined prospectively collected blood or stored plasma samples obtained before invasive diagnostic testing in patients identified by conventional methods of screening as being at high-risk for aneuploidies.…”
Section: Resultsmentioning
confidence: 99%
“…The first group of studies was used for the meta-analysis on the performance of screening by cfDNA testing in screening for aneuploidies [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40]. These studies reported cfDNA results in relation to fetal karyotype from invasive testing or clinical outcome; 26 studies examined prospectively collected blood or stored plasma samples obtained before invasive diagnostic testing in patients identified by conventional methods of screening as being at high-risk for aneuploidies.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining reads were considered unique reads for further analysis. To eliminate the effect of GC bias, we applied an integrated method for GC correction using a three-step process: LOESS regression (31), intrarun normalization (32), and linear model regression (33). Briefly, LOESS regression was used to smooth the sequencing bias produced by variable GC content on different chromosomes.…”
Section: Methodsmentioning
confidence: 99%
“…After normalizing the read count, one z-score per chromosome was calculated to determine fetal aneuploidy [5]. Most of published NIPT studies rely on the z-score which represents the quantitative variations of the chromosome of interest and they show the results as positive or negative by checking if the z-score exceeds the predefined threshold [6].…”
Section: Sequencing (Ngs) and Bioinformatics Led To A Novel Non-invasmentioning
confidence: 99%